2004
DOI: 10.1007/s00125-004-1418-3
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale studies of the HphI insulin gene variable-number-of-tandem-repeats polymorphism in relation to Type 2 diabetes mellitus and insulin release

Abstract: Aims/hypothesis. The class III allele of the variablenumber-of-tandem-repeats polymorphism located 5′ of the insulin gene (INS-VNTR) has been associated with Type 2 diabetes and altered birthweight. It has also been suggested, although inconsistently, that the class III allele plays a role in glucose-induced insulin response among NGT individuals. Methods. We investigated the impact of the class III allele on Type 2 diabetes susceptibility in a case-control study involving 1462 Type 2 diabetic patients and 493… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 38 publications
4
31
1
2
Order By: Relevance
“…The existence of noncanonical transcripts in transfected cells (Figs. 1B and 2A and C) and in EST libraries (online appendix Table 2) would be consistent with this concept, which appears to be further supported by the observed genetic linkage and allelic association of INS with type 1 diabetes (1) but not type 2 diabetes or other metabolic traits (24), except in childhood obesity (6). Subsequent studies should therefore examine each of these possibilities in greater detail, since alternative splicing and associated pathways might become suitable targets for therapeutic approaches in the future.…”
supporting
confidence: 69%
“…The existence of noncanonical transcripts in transfected cells (Figs. 1B and 2A and C) and in EST libraries (online appendix Table 2) would be consistent with this concept, which appears to be further supported by the observed genetic linkage and allelic association of INS with type 1 diabetes (1) but not type 2 diabetes or other metabolic traits (24), except in childhood obesity (6). Subsequent studies should therefore examine each of these possibilities in greater detail, since alternative splicing and associated pathways might become suitable targets for therapeutic approaches in the future.…”
supporting
confidence: 69%
“…In a general population, other authors also did not support associations between INS VNTR and body composition in childhood [25][26][27][28].…”
Section: Discussionmentioning
confidence: 85%
“…On the other hand, class III is protective against diabetes mellitus type 1 (T1DM) and leads to an overexpression of insulin [19][20][21]. Thus, it may be responsible for obesity, IR, T2DM, and polycystic ovary syndrome (PCOS); however, the results regarding the influence of INS VNTR polymorphism on these disorders, both in the general population and in SGA individuals, are divergent [10,13,15,17,[22][23][24][25][26][27][28][29]. The aim of the study was to verify whether INS VNTR class III allele is associated with low birth weight in the Polish population and to assess the influence of this variant on the current body mass index (BMI) as well as on the metabolic and hormonal profile in prepubertal SGA children.…”
Section: Introductionmentioning
confidence: 99%
“…In three British cohorts, Mitchell et al 48 did not find an association between INS VNTR size classes or evidence for parent-of-origin effects in the transmission of VNTR alleles. Similarly, Hansen et al 37 found that in a study of Danish Caucasians there was no association between genotype for INS VNTR alleles or for paternal or maternal transmission of class III alleles and birth weight. However, they did not compare average birth weights between class I and class III alleles according to parental origin.…”
Section: Discussionmentioning
confidence: 94%
“…34 Class III (4140 repeats) alleles exhibit a controversial association with type 2 diabetes predisposition, with some data supporting association with paternally transmitted alleles, 35 III/III homozygosity, 36 or no association at all. 37 Owing to a very high level of linkage disequilibrium (X94% concordance across populations 38,39 ) between the A/T single nucleotide poly- In this study, we investigated the association between small for gestational age birth (defined as o2540 g at term) and SNP variation at six sites in the INS and IGF2 genes in African-American subjects. We tested for association with SNP and haplotype genotypes in both the newborns and mothers and with the parental transmission of insulin haplotypes.…”
mentioning
confidence: 99%